Sigmund Freud analysis of a mind - A & E Home Video (Firm).; New Video Group ([United States] : A & E Home Video, 1995)
An extraordinary interview with Gloria Steinem highlights this in-depth portrait of the man whose controversial theories transformed our understanding of the mind and sexuality.
Title from title screen.
Keywords: Freud, Sigmund, -- 1856-1939 -- Videorecordings; Psychoanalysts -- Austria -- Biography; Biographical films; Biographical television program -- Videorecordings